Low temperature selective catalytic reduction of nitric oxide with urea over activated carbon supported metal oxide catalysts - Liu, Kaijie; Yu, Qingbo; Wang, Baolan; Qin, Qin; Wei, Mengqi; Fu, Qi (Environmental technology, 2020)
Selective catalytic reduction of nitrogen oxides (SCR) with loaded urea is a method for removing NO under oxygen-rich and low-temperature conditions, which can solve the inhibitory effect of oxygen on the catalyst and the slip of ammonia. In present study, a series of activated carbon (wo-AC, co-AC, cs-AC and nu-AC) supported metal (Mn, Fe, Co, Cu and Zn) oxide catalysts with loading urea were prepared by ultrasonic assisted impregnation. The catalysts were used for NO removal at 50-120°C and characterized by XRD, SEM, GFAAS, EDS, XPS, BET and FTIR techniques. The effects of activated carbon type, loaded active element, metal oxides loading, temperature fluctuation on catalytic activity and the catalytic stability were also studied in this paper. The results indicated that nutshell-based activated carbon was more suitable as a carrier than other activated carbons, and urea-10Mn/nu-AC catalyst yielded a higher NO conversion than other catalysts. Besides, for used activated carbons, the larger specific surface area, more micropores distribution and the larger number of hydroxyl group and cyano terminal group are beneficial to the catalytic process. Moreover, the downward trend of NO conversion with increasing temperature suggested the adsorption of reactant gases played a crucial role in the catalytic process of urea-SCR.